Seawater carbonate chemistry and measurements of foraminifera test morphology - Powers, Christopher; Paz, Alberto; Zyck, Amaelia; Harri, Kaylee; Geraci, Madison; Bernhard, Joan M; Zhang, Ying (PANGAEA, 2025)
In this study, laboratory treatments were conducted to examine the response of Haynesina sp., a benthic foraminifer identified from coastal sediments in Rhode Island, United States, to moderate and high acidification conditions. Thicknesses of foraminifera tests were mapped using X-ray tomography, enabling systematic comparisons throughout individual test chambers. The treatments were applied to both live and dead foraminifera, which provides an opportunity for examining the biotic and abiotic responses of foraminifera and their calcareous remains to coastal acidification. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were extracted from tables in the related paper (see Related to) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-08-14.
Keywords: Benthos; Calcification/Dissolution; Chromista; Coast and continental shelf; Containers and aquaria (20-1000 L or < 1 m**2); Foraminifera; Growth/Morphology; Haynesina sp.; Heterotrophic prokaryotes; Laboratory experiment; North Atlantic; Single species; Temperate